Clinical characteristics and acute complication of COVID-19 patients with diabetes: a multicenter, retrospective study in Southern China - Zhou, Xiao-ying; Huang, Shao-feng; Lin, Jun-xu; Zhi, Hai-ni; Xiao, Lu; Wang, Xiang-zhu; Guo, Kai-heng; Zhou, Lin; Long, Tao; You, Hui-min; Lin, Ming-run; Luo, Xiang-ya; et al. (Frontiers in Endocrinology, 2023)
Aims: This study aims to describe the clinical characteristics, laboratory data and complications of hospitalized COVID-19 patients with type 2 diabetes mellitus (T2DM) since epidemic prevention and control optimization was adjusted in December 2022 in China. Methods: This retrospective multicenter study included 298 patients confirmed type 2 diabetes mellitus with or without COVID-19. We collected data from the first wave of the pandemic in The Fifth Affiliated Hospital of Guangzhou Medical University, Loudi Central Hospital and The First People’s Hospital of Xiangtan from December 1, 2022 to February 1, 2023. We extracted baseline data, clinical symptoms, acute complications, laboratory findings, treatment and outcome data of each patient from electronic medical records. Results: For among 298 hospitalized patients with type 2 diabetes, 136 (45.6%) were COVID-19 uninfected, and 162 (54.4%) were COVID-19 infected. We found that the incidence of cough, fatigue, fever, muscle soreness, sore throat, shortness of breath, hyposmia, hypogeusia and polyphagia (all p<0.01) were significantly higher in the exposure group. They showed higher levels of ketone (p=0.04), creatinine (p<0.01), blood potassium (p=0.01) and more diabetic ketoacidosis (p<0.01). Patients with COVID-19 less use of metformin (p<0.01), thiazolidinediones (p<0.01) and SGLT2 (p<0.01) compared with patients without COVID-19. Conclusion: COVID-19 patients with diabetes showed more severe respiratory and constitutional symptoms and an increased proportion of hyposmia and hypogeusia. Moreover, COVID-19 patients with diabetes had a higher incidence of acute complications, are more prone to worsening renal function, and were more cautious about the use of antidiabetic drugs.